2009
DOI: 10.1007/s10808-009-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the melt flow direction on the treeing process in polymeric insulation

Abstract: UDC 678:621.315.61 V. A. Volokhin, O. S. Gefle, and S. M. LebedevThis paper presents the results of a study of the effect of the residual mechanical stress formed in solid polymers at the stage of production on the initiation and growth of an electrical tree. It is shown that the time to tree initiation and the time to breakdown of polycarbonate samples can be determined from the results of investigation of treeing parameters.Introduction. One of the main factors responsible for the failure of high-voltage pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…The conclusions of [51] are in qualitative agreement with those of [43]. The conclusions of [51] were confirmed with polycarbonate samples in a later publication [52], where it was pointed out that the melt flow directions and the fringe patterns may influence the direction and propagation of electrical trees. An indirect evidence of the above is offered in [53], where an investigation of the electrical trees in outer and inner layers of different voltage rating XLPE cable insulation indicated that the growth rate of electrical trees in a 66 kV cable is much larger than that in the higher voltage rating cables.…”
Section: Electrical Trees and Their Naturesupporting
confidence: 84%
“…The conclusions of [51] are in qualitative agreement with those of [43]. The conclusions of [51] were confirmed with polycarbonate samples in a later publication [52], where it was pointed out that the melt flow directions and the fringe patterns may influence the direction and propagation of electrical trees. An indirect evidence of the above is offered in [53], where an investigation of the electrical trees in outer and inner layers of different voltage rating XLPE cable insulation indicated that the growth rate of electrical trees in a 66 kV cable is much larger than that in the higher voltage rating cables.…”
Section: Electrical Trees and Their Naturesupporting
confidence: 84%
“…Properties of thermoplastic polymers can be changed in wide range not only depending on the type, chemical structure, and sub-molecular structure but also processing parameters [1][2][3][4][5][6][7]. When polymers are under a high temperature for a long time, the destruction or oxidation of macromolecules will take place.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, incorrect choice of the processing parameters can result in the deterioration of mechanical and electrical properties of polymeric products. For example, temperature, exposure time of a polymer under the melt and the cooling rate are the most significant factors at production of large-size insulation products by quasi-isothermal method [2,3]. At the processing of polymers by the injection molding such factors are temperature, pressure, and cooling rate [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation